Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Screening and optimisation of crude exopolysaccharide production by marine Brevibacterium sp. JAB08 isolated from the jellyfish Chrysaora sp. from the coastal waters of Goa - Balaji Vaishnavi; R. Amal; Biraja Kumar Sahu; S. V. Sandhya (Antonie van Leeuwenhoek, 2026)

Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Comparative evaluation of larval susceptibility of Culex quinquefasciatus and Culex gelidus to three formulations of Bacillus thuringiensis var. israelensis - Sandhya Ananth; S. Mahalakshmi; V. Pranav; Dharani Govindasamy; Ashwani Kumar (International Journal of Tropical Insect Science, 2026)

Impact of home gardens promoted among urban residents in Dhaka, Bangladesh - Pepijn Schreinemachers; Sandhya S. Kumar; Nasir Md. Uddin (Food Security, 2025)
Promoting gardening among urban residents holds the potential to improve urban diets in low- and middle-income countries, but there is a lack of evidence of impact. This study tests the hypothesis that training urban residents in gardening increases their intake of fruit and vegetables. It uses panel data for 254 control and 425 treatment households from four city corporations in the Dhaka metropolitan area of Bangladesh. Urban residents, 85% of whom were women, were interviewed before the start of an urban gardening program and one year after training and inputs were provided to the treatment group. The study estimated the average treatment effects using a difference-in-difference estimator. Of the 38 outcomes tested, 20 are significant (p < 0.05) with 19 indicating a beneficial effect and one indicating an adverse effect. Among the beneficial effects, there is an increase in the diversity of fruits and vegetables produced (+ 5 species, p < 0.01), the frequency of harvesting (+ 0.64 times/week; p < 0.01), and increased sharing of produce with neighbors (+ 8%, p < 0.01). Regarding food and nutrition, there is an increase in women’s dietary diversity score (+ 0.37 on a 0–10 scale; p < 0.01), women’s minimum dietary diversity (+ 4%; p < 0.01), and in the number of portions of cooked vegetables eaten (+ 0.96 portions/day; p < 0.01). The gardening intervention also contributes to a range of perceived social, personal, and psychological benefits. The adverse effect is an increase in ultra-processed food consumption (+ 19%, p = 0.04). Nevertheless, the results confirm that urban gardening interventions can improve the quality of urban diets alongside other benefits.

Production of non-embryogenic synthetic seeds for short-term cold storage and ISSR marker-assisted genetic fidelity analysis of Coleus forskohlii (Willd) Briq. plants - Mahesh Kumar Badhepuri; Mahender Aileni; Prabhakar Rao Beeravelli; Sathish Kumar Durgam; Dulam Sandhya; Mahipal S. Shekhawat; Nageswara Rao Singisala (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A paradigm assessment of low-cost ceramic membranes: Raw materials, fabrication techniques, cost analysis, environment impact, wastewater treatment, fouling, and future prospects - K.V.V. Satyannarayana; Randeep Singh; S. Lakshmi Sandhya Rani; M. Sreekanth; Vinoth Kumar Raja; Young-Ho Ahn (Journal of Water Process Engineering, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

Sedimentological responses to coastal dynamics along the Thane District, North Maharashtra, West Coast of India - Sridhar D. Iyer; A. R. Gujar; V. Sanil Kumar; D. K. Naik; S. S. Gaonkar; Sandhya Naik; Pooja Shirodkar; F. Badesab; R. A. A. Luis (Sustainable Water Resources Management, 2021)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Rational Design, Synthesis, and In Vitro Neuroprotective Evaluation of Novel Glitazones for PGC-1α Activation via PPAR-γ: a New Therapeutic Strategy for Neurodegenerative Disorders - Antony Justin; Subhankar Mandal; P. Prabitha; S. Dhivya; S. Yuvaraj; Pradeep Kabadi; Satheesh John Sekhar; C. H. Sandhya; Ashish D. Wadhwani; Selvaraj Divakar; Jeyabalan Jeyaram Bharathi; Priya Durai; et al. (Neurotoxicity Research, 2020)

Insecticidal activity of botanical oils and other neem-based derivatives against whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) on cotton - Rishi Kumar; Sandhya Kranthi; V. S. Nagrare; D. Monga; Keshav Raj Kranthi; Naveen Rao; Amarpreet Singh (International Journal of Tropical Insect Science, 2019)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)